Evaluasi Pelatihan Bisnis UMKM Pada UMKM Juara Di Dinas Koperasi Dan UKM Kabupaten Karawang Tahun 2023 - Siti Laela Qodariah; Enjang Suharman; Flora Patricia Anggela (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this research is to find out and analyze the results of the evaluation of MSME business training for Champion MSMEs at the Karawang Regency Cooperative and UKM Office in 2023. This type of research is descriptive qualitative with data analysis using the Krikpatrick model. The number of participants in this study were 22 people consisting of 12 MSME people who were selected as the best participants in May and June, 7 assistants and 3 people from the Karawang Regency Cooperative and UKM Office, namely the Head of Service, Head of Section and Head of Micro Business Development Section. . Where, the selection of participants was carried out using a purposive sampling strategy. Based on the results of the descriptive analysis, it shows that the implementation of MSME business training for UMKM Champion in Karawang Regency is in the good category. While the results of the analysis using the Krikpatrick model show that the evaluation that must be carried out results from the analysis using the Kirkpatrick model, namely at the reaction stage in the form of participation and consumption, then at the learning stage and at the results/impact stage, namely business improvement.